Macro-level entrepreneurship evaluation : methodological limitations versus research needs - Głodowska, Agnieszka (Ewaluacja przedsiębiorczości na poziomie makro : ograniczenia metodologiczne i potrzeby badawcze, 2018)
The purpose of the article is to present the results of the study on entrepreneurship and its evaluation at macro-level. The study is conducted in the context of the imperfections of indicators used and future research needs. The methods applied in the study are: the analysis and criticism of the literature on the subject. The starting point for the study is to conceptualize the entrepreneurship comprehensively. Then the article presents used measures of the entrepreneurship. Finally, there is an attempt to identify the directions for future research on entrepreneurship at macro-level. The query of literature on defining entrepreneurship and its measurement did not bring unambiguous results. Entrepreneurship is an extremely complex issue that causes a lot of methodological limitations. Establishing a modular indicator at country level can determine the development of the entrepreneurship research in general. It can have key meaning from cognitive as well as applied perspective.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 523, s. 138-149
Keywords: entrepreneurship; macrolevel; entrepreneurship of the country; GEM; przedsiębiorczość; makropoziom; przedsiębiorczość państwa